The Use of Solite Kids Interactive Learning Media to Improve Fiqh Learning Outcomes in Madrasah - Izzah Nur Hudzriyah Hasan; Imam Syafi’i; Muhammad Fahmi; Laili Mas Ulliyah Hasan (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2025)
Technological advancements in education require teachers to present engaging and enjoyable learning experiences that align with the characteristics of today’s digital generation. The use of technology-based learning media, such as Android applications, offers a solution for creating a more interactive and effective learning environment. This study aims to examine the effectiveness of the Android-based interactive learning media Solite Kids in improving student learning outcomes in the Fiqh subject for seventh-grade students at MTsN 3 Kota Surabaya. The research method used is a quasi-experimental design with a pretest-posttest control group format. Data were collected through pretest and posttest assessments administered to two classes: class VII G as the experimental group using Solite Kids, and class VII H as the control group using conventional teaching methods. Data analysis included normality testing, homogeneity testing, and an independent sample t-test using SPSS software. The results showed that the average posttest score of the experimental group increased to 80.17, while the control group achieved an average of 70.83. The independent sample t-test yielded a significance value (2-tailed) of 0.009 < 0.05, indicating that H₀ is rejected and Hₐ is accepted. Therefore, it can be concluded that the Android-based interactive learning media Solite Kids is effective in improving Fiqh learning outcomes among seventh-grade students at MTsN 3 Kota Surabaya. Keywords: Learning Media, Android Solite Kids, Fikih Learning Outcomes.